Analyzing the Secure Virtualization schemes and preventions from DDoS flooding Zoombie attacks - Chaturvedi, Amit K; Kumar, Punit; Sharma, Kalpana (International Journal of Computer Sciences and Engineering, 2019)
As Cloud computing emerges as a dominant paradigm in distributed systems, it is important to fully understand the underlying technologies that make clouds possible. One technology, and perhaps the most important, is the virtualization. Recently virtualization, through the use of hypervisors, has become widely used and well understood by many. Distributed Denial of Service (DDoS) attacks typically focus high quantity of IP packets at specific network entry elements; usually any form of hardware that operates on a Blacklist pattern is quickly overrun. As in the cloud computing, a large number of tenants or VM clients share the common hardware, DDoS attacks have the potential of having much greater impact than against single tenanted architectures. In this paper, various secure virtualization schemes and preventions from DDoS flooding zombie attacks are analyzed. Security threats are discussed and preventive measures from DDoS attacks and protection solutions are presented so that the companies can take the appropriate action accordingly.